Factors Affecting Women's Actioncouple of Age Age (PUS) About Examinationiva On Prevention of Services in Services Kecamatan Medan Johor Environment XV 2018 - Lubis, Rida Rumondang (Sari Mutiara Indonesia University Press, 2018)
Cervical cancer is a disease caused by HPV or human papilloma virus. IVA is a cervical examination directly (with the naked eye) after the administration of acetic acid will affect the abnormal epithelium where there will be an increase in osmolarity of extra celular fluid, which is hypertonikini which will draw fluid from the intra celular so that the cell membrane will collapse and the distance between the cells will get closer , consequently the reddish shadow of the blood vessels in the stroma will be closed and the cervix will appear whiter. Descriptive analytic research design with Cross Sectional approach is a study to study the dynamics of correlation between risk factors with the effect of how to approach, observe and collect data at once. The population in this study were women pus in the johor ward XV field district with a total of 134 respondents. The sample in this study uses total sampling. Based on the results of the study of knowledge obtained the Chi-Square test (-value) = 0.011 <0.05, the age obtained by Chi-Square test (-value) = 0.047 <0.05. education obtained by Chi-Square test (-value) = 0.045 <0.05. parity obtained by Chi-Square test (-value) = 0.000 <0.05, attitudes obtained by Chi-Square test (-value) = 0.000 <0.05. From the results of the second stage of logistic regression, namely the attitude of women pus with value (sig = 0,000; Odd Ratio 7,532). The conclusion of the results of the study is the influence of knowledge, age, education, parity, and attitudes with IVA examination. And the most influential factor in the SADARI examination is knowledge, parity and attitudes of women.